2022
DOI: 10.2217/fmb-2021-0108
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Formation of Panresistant Klebsiella Pneumoniae

Abstract: Introduction: The authors aimed to investigate the biofilm-forming features of panresistant Klebsiella pneumoniae (PRKp). Material & methods: The biofilm formations were shown under light microscope and laser scanning confocal microscopy. The optical densities of the wells were measured and classified according to biofilm-forming capacities. Results: The ratio of biofilm-forming K. pneumoniae was established to be 100%. All isolates were found to form high-level biofilms in classification compared with pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Ashwath et al found that 97.1% of the clinically multidrugresistant (MDR) K. pneumoniae isolates formed biofilms, and the isolates from blood, pus and trachea secretions were more capable of forming biofilms (Ashwath et al, 2022). Tuncer et al investigated biofilm-forming features of pan-resistant (resistant to all agents) K. pneumoniae and found that all the isolates formed high-level biofilms, whereas no significant difference was detected for the isolates obtained from different samples (blood, sputum and wound) (Tuncer et al, 2022). Differences between different studies may attribute to geographic regions, sample types and numbers, and bacterial antibiotic resistance.…”
Section: Biofilm and Its Association With Antibiotic Resistancementioning
confidence: 99%
“…Ashwath et al found that 97.1% of the clinically multidrugresistant (MDR) K. pneumoniae isolates formed biofilms, and the isolates from blood, pus and trachea secretions were more capable of forming biofilms (Ashwath et al, 2022). Tuncer et al investigated biofilm-forming features of pan-resistant (resistant to all agents) K. pneumoniae and found that all the isolates formed high-level biofilms, whereas no significant difference was detected for the isolates obtained from different samples (blood, sputum and wound) (Tuncer et al, 2022). Differences between different studies may attribute to geographic regions, sample types and numbers, and bacterial antibiotic resistance.…”
Section: Biofilm and Its Association With Antibiotic Resistancementioning
confidence: 99%